Tunable Fano and coupled-resonator-induced transparency resonances in the waveguide-coupled inverted nested ring resonator. (14th November 2017) - Yu, Changqiu; Tian, He; Qian, Zhenghong; Bai, Ru; Zhu, Liyao; Zhang, Yundong
Abstract: A waveguide-coupled inverted nested ring resonator structure is proposed and theoretically investigated. The effects of the parameters of such a structure on its transmission properties are demonstrated. Results show that both Fano resonance and coupled-resonator-induced transparency (CRIT) spectra can be produced within this structure, depending on the length ratio of the feedback waveguide and ring. In addition, the slope of the Fano resonance can be tuned and reversed by varying coupling coefficients and effective refractive index. Besides, CRIT-based tunable group delay can be obtained with high transmittance. Therefore, this structure has potential applications in optical sensors and optical communication.